Factors Associated with Complications of Snakebite Envenomation in Health Facilities in the Cascades Region of Burkina Faso from 2016 to 2021 - Rene Kinda; Sidikiba Sidibe; Dramane Zongo; Tieba Millogo; Alexandre Delamou; Seni Kouanda (Tropical Medicine and Infectious Disease)
Snakebite envenomation remains a major cause of morbidity and mortality in rural populations. This study identified factors associated with the complications of snakebite envenomation reported in the Cascades region of Burkina Faso. This cross-sectional study used the routine data of patients admitted for snakebite envenomation at five health facilities between 1 January 2016 and 31 December 2021. Data were collected on sociodemographic, clinical, and therapeutic characteristics of patients with signs of envenomation. Bivariate and multivariate analyses were conducted to identify factors associated with complications. Among the 846 patients with envenomation, 355 (42%) experienced complications. Local complications (23.2%, 196/846) included wounds and skin necrosis, whereas systemic complications (34.3%, 290/846) included hemorrhage, shock, and coma. Of all complicated cases, 7.6% (27/355) died. Factors associated with complications were rural residence (AOR: 4.80; 95% CI: 2.21–11.4), incision at the bite site (AOR: 4.31; 95% CI: 2.51–7.52), tourniquet application (AOR: 5.52; 95% CI: 1.42–30.8), bleeding (AOR: 14.2; 95% CI: 8.80–23.4), abnormal vital signs (AOR: 14.3; 95% CI: 9.22–22.7), and lack of antivenom administration (AOR: 2.92; 95% CI: 1.8–4.8). These findings highlight the importance of antivenom availability and public awareness for reducing the incidence of complications of snakebite envenomation.